Impact of peat thermal treatment on oil removal from water surface - Chukhareva N. V. Natalia Vyacheslavovna (Ecology and environmental protection, 2016)
The capacity of air-dried and heat-treated peat sorbent to destroy oil on the water surface was studied. Physiological groups of bacteria and microorganisms from raw and oil contaminated peat extracts which were in contact with oil and drinking water from centralized supply systems during two months were defined. The number of bacteria was defined by the titration method in liquid medium and calculating the colonies in solid medium. The degree of solute natural destruction was defined regarding evaporation of light fractions of hydrocarbons, degree of water contamination with oil was determined by fluorimetric method. In addition, it was revealed that heat treatment of peat samples has impact on bacterium activity. Based on the obtained data, the oligotrophy index was calculated in order to determine the balanced character of bacterial processes and prevalence of organic matter destruction over its accumulation. The use of thermally treated peat with increased sorption capacity allows decreasing concentration of petroleum hydrocarbon in water.